Investigation of Wide Band Modified Bowtie Antenna - Hussain, Sayed Mayed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The wide band width is one of the most demanding characteristic of patch antennas in the current advanced technology and research studies. Several studies on improving the bandwidth of patch antennas have been reported in the literature. Spiral patch antenna, fractal patch antenna and bowtie patch antenna are among the major configurations that are investigated primarily for improving the bandwidth of patch antennas. Bowtie patch antenna has the simplest layout that is used for its wide bandwidth and significant antenna for improving bandwidth and gain. Perfect Electric Conductor (PEC) with a Taconic TLY-5 as a substrate with 0.79 mm thickness are used in the simulations in this thesis. Three different modifications are used in the simulations to improve the bandwidth and gain of a simple 2x2 bowtie array. 1st modification which involves a slot with different lengths increase the bandwidth from 5.09 % to 8.62 % and gain from 13.4 dB to 13.7 dB. 2nd modification is applied to the feed network to make the antenna radiation symmetrical which increased the bandwidth from 5.09 % to 5.91 % but decreased the gain to 12 dB. 3rd modification involves a combination of the first two modifications that would make the antenna radiation symmetrical, increase bandwidth from 5.09 % to 9.51 % and increase the gain from 13.4 to 13.7 dB. The simulations cover the X-band region.

ÖZ: Mevcut yüksek teknoloji ve araştırma konusu, patch antenleri ve patch antenlerinin en önemli bir özelliklerinden olan geniş bantgenişliğinin araştırılmasıdır. Yapılan araştırılmalarda bantgenişliğinin geliştirilmesi üzerine çalışılmış ve rapor edilmiştir. Spiral patch antenler, fractal patch antenler ve bowtie patch antenler ana konfigurasyonlar olarak tanımlanır ve araştırmalar bu antenler üzerine yapılarak patch antenlerin bant genişlikleri geliştirilmiştir. Bowtie patch antenler en basit mizanpaj’a sahiptirler. Bu sebeple, patch antenlerin bantgenişliklerinin geliştirilmesinde ve kazancında önemli bir payı vardır. Bu tezde, kalınlığı 0.79 mm olan Taconic TLY-5 alt katmana sahip bir Perfect Electric Conductor (PEC) kullanılarak simulasyon araştırması yapılmıştır. Similasyonda üç farklı modifikasyon kullanılanılarak 2x2 bowtie dizisinin kazancı ve bant genişliği geliştirilmiştir. Ilk modifikasyonda farklı uzunlukların olduğu yarıklar kullanılarak bantgenişliği % 5.09’dan % 8.62’ye, kazanç ise 13.4 dB’ den 13.7 dB’ye çıkarılmıştır. Ikinci modifikasyonda feed network uygulanarak anten radyasyonları simetrik yapılmıştır. Böylece bantgenişliği % 5.09’dan %5.91’e yükseltilmiş fakat kazanç 12 dB’ e düşmüştür. Üçüncü modifikasyon ise bahsi geçen ilk iki modifikasyonun birleşimi ile yapılmıştır. Bu sayede anten radyasyonları simetrik yapılmış ve bantgenişliği % 5.09’dan % 9.51’e kazanç ise 13.4 dB’ den 13.7 dB’e kadar yükseltilmiştir. Simülasyon X-band bölgesini kapsamaktadır.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Prof. Dr. Şener Uysal.
Keywords: Electrical and Electronic Engineering; Antennas; Modified bowtie patch antenna array; high bandwidth; improved gain; symmetric antenna; simple array; X-band